Development and evaluation of a rapid detection assay for severe fever with thrombocytopenia syndrome virus based on reverse-transcription recombinase polymerase amplification. (August 2020) - Zhou, Jingyu; Wang, Qiujing; Zhu, Lijun; Li, Shibo; Li, Wei; Fu, Yongfeng; Cheng, Xunjia
Abstract: Rapid detection of severe fever with thrombocytopenia syndrome virus (SFTSV) is crucial for its control and surveillance. In this study, a rapid isothermal real-time reverse-transcription recombinase polymerase amplification (RT-RPA) assay was developed for the detection of SFTSV. The detection limit at 95% probability was 241 copies per reaction. A test of 120 serum samples of suspected severe fever with thrombocytopenia syndrome (SFTS) patients revealed that the sensitivity and specificity of the RT-RPA assay was approximately 96.00% (95%CI: 80.46%–99.79%) and 98.95% (95% CI: 94.28%–99.95%), respectively; the kappa value was 0.9495 (P＜0.001). The Bland-Altman analysis showed that 87.50% of the different data points were located within the 95% limits of agreement, indicating a good correlation between the results from RT-RPA assays and those of RT-qPCR assays. In conclusion, the rapid and efficient RT-RPA assay can be a promising candidate for point-of-care detection method of SFTSV. Highlights: A RT-RPA assay was developed to detect SFTSV RNA isothermally. The assay can rapidly produce a result in 15 min at 39 °C. The detection limit of the assay is 241 RNA sequences. The results of RT-RPA compare well with RT-qPCR. The RT-RPA assay may be used for field detection of SFTSV in resource-limited settings.